Physical test and irritation test of water guava leaf extract (Syzygium aqueum) as a natural spray hand sanitizer - Sofya, Sri Winarni; Muhsin, Lalu Busyairi (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
This study explores the manufacture of water guava (Syzygium aqueum) leaf extract-based hand sanitizers as an effective and safe natural alternative for maintaining hand hygiene. Given the importance of hand hygiene in preventing the spread of disease, especially amid the COVID-19 pandemic, the use of hand sanitizers has increased significantly. However, alcohol-based products are often irritating to the skin. Therefore, this study aims to evaluate the potential of water guava leaf extract to improve the effectiveness and convenience of hand sanitizers. Water guava leaves contain active compounds such as flavonoids, tannins, and phenolics with antibacterial and anti-inflammatory properties. The research method includes extracting water guava leaves, hand sanitizer formulation, and organoleptic, pH, homogeneity, and irritation testing. The tests carried out were physical tests, including organoleptic tests (shape, smell, and colour), pH, homogeneity, spreadability, adhesiveness, and product irritation tests. The research was designed with a posttest-only control group design with true experimental by analyzing the test object after being given treatment. This research is expected to produce products that are useful for the community. The results showed that all hand sanitizer formulas tested had a pH within the safe range of pH 5 for the skin without irritating the skin of the test animals. Formulas with added guava extract showed improved aroma and anti-irritation, with formulas F1 and F2 gaining the highest preference in aroma and colour. This study concludes that water guava leaf extract can be effectively used in the manufacture of hand sanitizers, providing a gentler and skin-friendly alternative to alcohol-based synthetic products.